Shaktism: Exploring the Evolution and Significance of Shaktism: A Study of Goddess Worship and Cultural Evolution (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Shaktism in which the highest place was accorded to the female principle was the faith of a large number of people all over the continent. The goddess of Shakti was worshipped with different names: most popular was the mother goddess. The origin of Shaktism evolved out of the pre-historic mother goddess cult symbolizing the facts of primitive life.